A novel wheat bZIP transcription factor, TabZIP60, confers multiple abiotic stress tolerances in transgenic Arabidopsis. Issue 4 (18th October 2014) - Zhang, Lina; Zhang, Lichao; Xia, Chuan; Zhao, Guangyao; Liu, Ji; Jia, Jizeng; Kong, Xiuying
Abstract : The basic region/leucine zipper (bZIP) transcription factors (TFs) play vital roles in the response to abiotic stress. However, little is known about the function of bZIP genes in wheat abiotic stress. In this study, we report the isolation and functional characterization of the TabZIP60 gene. Three homologous genome sequences of TabZIP60 were isolated from hexaploid wheat and mapped to the wheat homoeologous group 6. A subcellular localization analysis indicated that TabZIP60 is a nuclear‐localized protein that activates transcription. Furthermore, TabZIP60 gene transcripts were strongly induced by polyethylene glycol, salt, cold and exogenous abscisic acid (ABA) treatments. Further analysis showed that the overexpression of TabZIP60 in Arabidopsis resulted in significantly improved tolerances to drought, salt, freezing stresses and increased plant sensitivity to ABA in seedling growth. Meanwhile, the TabZIP60 was capable of binding ABA‐responsive cis ‐elements that are present in promoters of many known ABA‐responsive genes. A subsequent analysis showed that the overexpression of TabZIP60 led to enhanced expression levels of some stress‐responsive genes and changes in several physiological parameters. Taken together, these results suggest that TabZIP60 enhances multiple abiotic stresses through the ABA signaling pathway and that modifications of its expression may improve multiple stress tolerances in crop plants.